KONTRUKSI SOSIAL MASYARAKAT MANDAR TERHADAP PASSAU’ WAI DI DAERAH ALIRAN SUNGAI (DAS) MANDAR - Nur Fitriani Maskur (Journal of Innovation Research and Knowledge, 2025)
Mandar defined as water, thus Mandarnese society is a community that closely related to the water, which is formed from seven kingdoms upstream and seven kingdoms downstream of the river "pitu ulunna salu, pitu baqbana binanga". The society and Mandar River are two things that cannot be separated from the past until nowadays. This research is focused on the investigation of the people context who work as passau’ wai, the social construction of the passau' wai in the Mandar River watershed, the environmental conditions of the Mandar River, and the value implementationof the passau’ wai.The subject of analysis is the head of the family who is passau’ wai by profession. The results show that the current condition of the Mandar River is in a polluted status, the condition of the river does not discourage the community from continuing to carry out “passau 'wai” activities. The social construction process that formed is the influence of the Mandar community's paradigm which assumes that Mandar River water is a medicine or an antidote. The social context of the people who work as passau' wai was motivated by some factors, they are low education, habit, distance from the house to the river, and economic conditions. The activity of “massau' wai” is one of the ancestral cultures which in the process contains values, namely, 1) religion, 2) value of belief, 3) togetherness, 4) humanity, 5) Siri' (shame), 6) high work ethic, 7) mutual cooperation, and 8) Sibaliparriq (gender equality).